Tencent : The political economy of china's surging internet giant - Tang, Min (New York : Routledge, 2020)
"In this book, author Min Tang examines the political economy of the China-based leading global Internet giant, Tencent. Tracing the historical context and shaping forces, the book illuminates Tencent's emergence as a joint creation of the Chinese state and transnational financial capital.
History and context, Economic profile, Political profile, Cultural profile.
Includes bibliographical references and index.
Keywords: Internet Economic aspects